Linking the 2030 Agenda for Sustainable Development to Research, Newspapers, and Governance: The Case of the Last Free-Flowing Alpine River - Scaini, Anna; Scaini, Chiara; Frentress, Jay; Destouni, Georgia; Manzoni, Stefano (Frontiers in Environmental Science, 2021)
Are academic, newspaper and regulatory documents aligned with the UN Sustainable Development Goals (SDGs) and the Sendai Framework for Disaster Risk Reduction (SENDAI)? To answer this question, we develop a framework to compare the most commonly occurring keywords across these document types, as well as their use of SDG and SENDAI keywords. The approach is tested in a case study on the Tagliamento River in the Italian Alps to explore the degree of communication among academia, newspapers and governance. Across the analyzed documents, we found disconnection between academic sources and regulatory documents. Occurrences of SDG- related keywords are positively correlated in regulatory documents and newspapers (r = 0.6), and in academic literature and newspapers (r = 0.38), indicating some degree of agreement. However, no correlation emerges between academic and regulatory documents, indicating a critical gap for communication and understanding between academic research and governance.